Complete Right Lung Agenesis with Dextrocardia: An Unusual Cause of Respiratory Distress - Nandan,Devki; Bhatt,Girish Chandra; Dewan,Vivek; Pongener,Imkongkumzuk
Pulmonary agenesis, defined as complete absence of bronchus, parenchyma, and vessels is a very rare condition. Herein, we report a 4-month-old infant who presented with fever, cough, and respiratory distress and was misdiagnosed in a peripheral hospital as a case of pneumonia. The child was, later diagnosed as having right lung agenesis with dextrocardia.